2022
DOI: 10.25259/sni_948_2021
|View full text |Cite
|
Sign up to set email alerts
|

Transtentorial spread of glioblastoma multiforme to cerebellopontine angle – A rare case report

Abstract: Background: Glioblastoma multiforme (GBM) is the most common central nervous system malignant tumor in adults with 48.3% of cases. Despite it, the presence of transtentorial spread is uncommon, with few patients reported in the literature. In this study, the authors report a case of GBM transtentorial spread to cerebellopontine angle after resection and adjuvant treatment. Case Description: A 55-year-old male patient with GBM, previously submitted to surgical resection and adjuvant treatment with radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The presence of CTCs in GBM has been a topic of discussion for many years. GBM is known for its high aggressiveness and invasiveness, but it predominantly remains localized to the brain, with extracranial metastases being extremely rare, affecting only 0.5-2% of patients and typically involving sites like the lungs, bone, lymph nodes, or liver [30][31][32][33][34][35][36]. Mounting evidence has shown that the presence and quantity of CTCs in bodily fluids are associated with glioblastoma progression, treatment response, and patient survival, indicating their potential as diagnostic and prognostic biomarkers.…”
Section: Circulating Tumor Cells As Glioblastoma Biomarkersmentioning
confidence: 99%
“…The presence of CTCs in GBM has been a topic of discussion for many years. GBM is known for its high aggressiveness and invasiveness, but it predominantly remains localized to the brain, with extracranial metastases being extremely rare, affecting only 0.5-2% of patients and typically involving sites like the lungs, bone, lymph nodes, or liver [30][31][32][33][34][35][36]. Mounting evidence has shown that the presence and quantity of CTCs in bodily fluids are associated with glioblastoma progression, treatment response, and patient survival, indicating their potential as diagnostic and prognostic biomarkers.…”
Section: Circulating Tumor Cells As Glioblastoma Biomarkersmentioning
confidence: 99%